Community-Acquired Pneumonia Due to Virus and Mycoplasma pneumoniae Infection in Children Younger than 5 Years - Sun, Huiming; Zhu, Wenqing; Chen, Zhengrong; Ji, Wei; Hao, Chuangli; Xinxing, Zhang; Wenjing, Gu; Wang, Yuqing (Journal of Pediatric Infectious Diseases, 2019)
The purpose of this study was to determine the clinical features of viral pathogens and Mycoplasma pneumoniae in children hospitalized with community-acquired pneumonia (CAP). M. pneumoniae infection was diagnosed by both serology and polymerase chain reaction (PCR). Respiratory viruses were detected by direct immunofluorescence or PCR. Medical records of children younger than 5 years diagnosed with 5-day-old CAP were reviewed. Viral pathogens and/or M. pneumoniae were detected in 388 (15.59%) children in the following three groups: viral monoinfection (n = 321), M. pneumoniae with viral coinfection (n = 17), and M. pneumoniae monoinfection (n = 50). M. pneumoniae monoinfection was characterized by older age, fever, higher neutrophil count, and chest X-ray showing lobar consolidation. Wheezing was more common in children with viral infections. Elevated alanine aminotransferase and aspartate aminotransferase were commonly seen in children with Mycoplasma infections. The median symptom duration in children with viral coinfection was shorter than in the other two groups (both p < 0.05). M. pneumoniae and respiratory viruses are important etiologic agents for CAP in children younger than 5 years, with characteristic clinical features. M. pneumoniae and viral coinfection are associated with shorter duration of symptoms before admission.
Keywords: coinfection; Mycoplasma pneumoniae; virus